An Atypical Case of Familial Glucocorticoid Deficiency without Pigmentation Caused by Coexistent Homozygous Mutations in MC2R (T152K) and MC1R (R160W) - BEREKET, ABDULLAH; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (ENDOCRINE SOC, 2012)
Context: Familial glucocorticoid deficiency (FGD) is a rare autosomal recessive disorder characterized by isolated cortisol deficiency. Mutations in the gene encoding the ACTH receptor (MC2R) account for 25% of cases. One significant feature is generalized skin hyperpigmentation, which is thought to be due to elevated ACTH acting on the melanocortin 1 receptor (MC1R). Objective: The aim of the study was to determine the cause of a nonhyperpigmented case of FGD. Patients: The patient presented at 4 yr of age with hypoglycemia after prolonged fasting during a respiratory tract infection. She had further hypoglycemic attacks and was diagnosed with isolated glucocorticoid deficiency at 6 yr of age. Her parents were consanguineous, and she had two unaffected sisters. Her physical examination was normal, except that her height and weight were greater than the 97th centile for a sex-and age-matched reference population. Interestingly, she had no hyperpigmentation despite very high ACTH levels. Results: Nucleotide sequence analysis revealed homozygous mutations c.478C>T in MC1R and c.455C>A in MC2R leading to R160W and T152K changes in the amino acid sequences, respectively. The R160W MC1R change has previously been implicated in a red hair/pale skin phenotype, and MC2R-T152K is trafficking defective. Both parents and two unaffected sisters were heterozygous for the MC1R mutation; additionally, one unaffected sister was heterozygous for the MC2R mutation, and the other was wild-type. Conclusion: We report an unusual case of FGD without hyperpigmentation due to coexistent MC1R/MC2R mutations. This case is important because it demonstrates for the first time that the assumption that the action of ACTH on MC1R causes skin hyperpigmentation is correct. (J Clin Endocrinol Metab 97: E771-E774, 2012)
Keywords: MELANOCORTIN 1 RECEPTOR; ADDISONS-DISEASE; RED HAIR; ADRENOCORTICOTROPIN RECEPTOR; ADRENAL INSUFFICIENCY; VARIANTS; HYPERPIGMENTATION; HUMANS; TYPE-1; GENE